Liquid–Liquid Extraction of Actinides from Nitric Acid Feeds Using Two Hexa-n-alkylnitrilotriacetamides. Issue 4 (7th June 2022) - Karak, Ananda; Mahanty, Bholanath; Mohapatra, Prasanta K.; Egberink, Richard J. M.; Valsala, T. P.; Sathe, D. B.; Bhatt, R. B.; Huskens, Jurriaan; Verboom, Willem
ABSTRACT: Solutions of two nitrilotriacetamide (NTA) ligands, viz., N, N, N', N', N", N" -hexa- n -butylnitrilotriacetamide (HBNTA) and N, N, N', N', N", N" -hexa- n -hexylnitrilotriacetamide (HHNTA) in 20% isodecanol–80% n -dodecane were employed for the extraction of U(VI), Np(IV), Pu(IV), and Am(III) from nitric acid feed solutions. Limitations of ligand solubility and third-phase formation when contacted with nitric acid solutions led to the choice of the diluent composition of 20% isodecanol and 80% n -dodecane. The results of the solvent extraction studies indicated poor extraction of the metal ions with HBNTA as compared to that with HHNTA as the extractant and hence, major part of this work involved HHNTA. Slope analysis suggested extraction of 1:1 (ML) species with Np(IV) and Pu(IV) at 3 M HNO3 and mixed 1:2 (ML2 ) and 1:3 (ML3 ) species with U(VI) at pH 2. At 0.5 M HNO3, the observed trend for extraction was Pu(IV) > Np(IV) >> Am(III) > U(VI).